Influence of Family Conversation Behaviour Towards Parents Mental Health in Kitere Hill, Rongo, Kenya - Okuthe Awuor Pelesiah; James Onyango Abila (African Journal of Education,Science and Technology (AJEST), 2025)
Conversation is essential to the success of every interaction, it is a dynamic process that takes place all the time, one of the developmental communication areas that may desire dynamic conversation is family conversation. Conversation shape individuals throughout their lives, and it is the foundation of family life and functioning. A family without a well-structured conversation, is likely to experience mental health challenges, mental health challenges have introduced fear, anxiety, uncertainties and anger. The purpose of this study was to examine the influence of family conversation behaviour on family mental health of parents in Kitere Hill. The study was guided by the following objective: to examine the influence of family conversation behaviour on mental health of parents in Kitere hill. The study was anchored on interaction theory, study location was Kitere Hill, Rongo, Sub County. It employed a descriptive research design with a qualitative approach, convenience sampling was applied to identify participants. Data was collected using interviews and analyzed using Nvivo. Thematic analysis revealed five key behaviours, availability, listening, open conversation, feedback and empathy, that significantly shaped parental mental well-being. The findings, grounded in symbolic interactionism, underscore the role of family interactions in constructing emotional meaning and psychological resilience. In resource-limited settings like Kitere Hill, conversation within the family unit can serve as a protective mechanism for mental health. This study highlights the need to integrate conversation-based approaches in community mental health programs and family support policies. The findings are expected to provide insights on enhancing conversation approach in family mental health. The study is significant to the achievement of Sustainable Development Goal number 3, “Ensure healthy lives and promote well-being for all at all ages.